An Overview on the Taxonomy, Phylogenetics and Ecology of the Psychedelic Genera Psilocybe, Panaeolus, Pluteus and Gymnopilus - Strauss, Dominique; Ghosh, Soumya; Murray, Zurika; Gryzenhout, Marieka (Frontiers in Forests and Global Change, 2022)
Psilocybin and psilocin, two psychoactive components found in “magic mushrooms”, have therapeutic potential in a number of mental health disorders without the addictiveness and overdose risks found in other mind-altering drugs, such as cocaine, methamphetamines and alcohol. Psychedelic mushrooms occur naturally, are wide distributed and easily accessible. The need for reviews and comprehensive field guides is urgent due to the recent surge of research into psychedelic mushrooms along with public interest. Psilocybin and psilocin are recorded in mushroom species of Psilocybe, Panaeolus, Pluteus and Gymnopilus. This review discusses species identification, taxonomy and classification, available DNA sequence data and psychedelic species in Psilocybe, Panaeolus, Pluteus and Gymnopilus, as well as similar looking genera that could be harmful.